Cystatin capture ELISA inmunodiagnosis of human fasciolosis at Chupaca-Junin province - Cornejo, William (2003)
Objective: To determine the prevalence of human fasciolosis in an endemic area by means of an enzyme-linked immunosorbent assay (ELISA) using cystatin as a capture agent for the detection of specific antibodies to Fasciola hepatica cysteine proteinases. Material and methods: An ELISA plate was sensitized with cystatin, incubated with excretory-secretory products of adult flukes, and followed by standard ELISA procedures. Clinical applicability of the cystatin capture ELISA for the immunodiagnosis of fasciolosis was tested with 200 serum samples of children and adults from an endemic area in Chupaca province, Junin department. Results: Serum samples from the endemic area tested by cystatin capture ELISA showed 27/ 200 (13,5%) of positive cases. Conclusions: Fasciolosis remains a major health problem at Chupaca province, Junin department.